2015
DOI: 10.1007/s00338-015-1330-y
|View full text |Cite
|
Sign up to set email alerts
|

Pelagic larval duration and settlement size of a reef fish are spatially consistent, but post-settlement growth varies at the reef scale

Abstract: Recent research has demonstrated that, despite a pelagic larval stage, many coral reef fishes disperse over relatively small distances, leading to well-connected populations on scales of 0-30 km. Although variation in key biological characteristics has been explored on the scale of 100-1000 s of km, it has rarely been explored at the scale relevant to actual larval dispersal and population connectivity on ecological timescales. In this study, we surveyed the habitat and collected specimens (n = 447) of juvenil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 75 publications
(87 reference statements)
0
8
0
Order By: Relevance
“…Third, the study does not provide any insights into population connectivity beyond the first few months of the juvenile stage (i.e., up to adulthood). The fates of recruits are likely to vary across sites given local ecological conditions (Leahy et al 2015), thus modifying the strength of population connections suggested by larval dispersal. However, determining patterns of full demographic connectivity was beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, the study does not provide any insights into population connectivity beyond the first few months of the juvenile stage (i.e., up to adulthood). The fates of recruits are likely to vary across sites given local ecological conditions (Leahy et al 2015), thus modifying the strength of population connections suggested by larval dispersal. However, determining patterns of full demographic connectivity was beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Chaetodon vagabundus (vagabond butterflyfish, Family Chaetodontidae) has a pelagic larval duration (PLD) of about 3 to 4 weeks (Leahy et al 2015), similar to a wide range of reef-fish species in the Indo-Pacific (Lester and Ruttenberg 2005). Adults of the species are territorial mid-water spawners that form strong pair bonds (Tanaka 1992).…”
Section: Study Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Established macroalgal beds can be highly persistent due to positive feedbacks that inhibit grazing and the settlement, growth, and survival of other reef organisms, including corals (Hoey & Bellwood ; Dell et al ) and some fishes (Leahy et al ). Large stands of upright macroalgae have been shown to discourage entry of herbivorous fishes, positively reinforcing macroalgal dominance (Hoey & Bellwood ).…”
Section: Biology Of Macroalgae On Coral Reefsmentioning
confidence: 99%
“…The allelochemicals can directly influence coral fitness through physiological deterioration of coral tissues (Rasher & Hay 2010;Rasher et al 2011), the inhibition of coral recruitment (Bulleri et al 2018), and by shifting associated microbial communities to predispose them to bleaching, infection, and mortality (Pantos et al 2003;Bourne et al 2009). Established macroalgal beds can be highly persistent due to positive feedbacks that inhibit grazing and the settlement, growth, and survival of other reef organisms, including corals (Hoey & Bellwood 2011;Dell et al 2016) and some fishes (Leahy et al 2015). Large stands of upright macroalgae have been shown to discourage entry of herbivorous fishes, positively reinforcing macroalgal dominance (Hoey & Bellwood 2011).…”
Section: Algal Categorymentioning
confidence: 99%